Predicting young Chinese consumers' intentions to purchase Western brands: Structural model analysis. - Fei Long; Miraj Ahmed Bhuiyan; Norzalita Abd Aziz; Muhammad Khalilur Rahman (PLoS ONE)
This study aims to investigate how young Chinese consumers make purchase intentions towards Western brands under the influence of two conflicting values and CSR, which is insufficiently discussed in the current literature. Both value-attitude-behavior (VAB) and consumer cultural theories are adopted to construct the research framework. Data was collected from undergraduate students studying at a public university located in Guangzhou via WeChat and Tencent QQ. A total of 314 usable responses were analyzed by the partial least squares structural equation modeling (PLS-SEM). The empirical findings indicated that cosmopolitanism has a significantly positive effect on brand attitudes and purchase intentions; ethnocentrism has a significantly negative effect on purchase intentions, but no significant impact on brand attitudes; and corporate social responsibility (CSR) initiatives positively affect brand attitudes rather than purchase intentions. The results also revealed that brand attitudes mediate the relationship between cosmopolitanism/CSR and purchase intentions, but it does not have a mediating effect on the relationship between ethnocentrism and purchase intentions. These findings provide essential insights to the body of knowledge of international marketing in emerging markets and shed light on understanding how young Chinese consumers make purchase decisions towards Western brands. The results are useful for Western brands to effectively adjust their marketing strategies and advertising/promoting campaigns for business development purposes in the Chinese market.